Turbine blade strike tests for evaluation and optimization of fish-friendly turbine. Issue 1 (1st June 2022) - Meng, L; Chen, R; Wang, X; Zhang, C Y; Zheng, Y; Tian, Y J
Abstract: Widening the knowledge for fish injury and mortality mechanism caused by pressure, shear stress and blade strikes inside turbine was constructive for optimizing fish-friendly turbine design and turbine operation regime. A special designed test equipment was applied for simulating the rotating blade inside turbine passage, anesthetized fish (crucian carp) was placed on the route of the blade for strike tests. The fish length, blade thickness, strike angle, and strike speed were independent variables during the tests, the injury rate, degree of injury and mortality rate were analysed according to observation or anatomical examination after repeated tests. The injury types were classified into: imbalance, ribs broken, gill cover broken, internal hemorrhage and death. The injury severity was directly affected by strike speed under same blade thickness and fish length. The ratio of blade thickness and fish length also affect the injury rate. Multiple injuries can be observed on one fish after tests, and combined injuries are more likely to lead to death. In the fish-friendly turbine design, blade thickness in the leading edge and blade numbers shall be carefully considered and the rotational speed shall be calculated.